Unraveling sugarcane-Diatraea saccharalis-opportunistic fungi interaction in sugarcane - Franco, Flávia Pereira (2017)
Plants respond to insect and pathogen attack by inducing and accumulating a large set of defense proteins. Colonization of sugarcane stalk by opportunistic fungi, such as Fusarium verticillioides and Colletotrichum falcatum, usually occurs after Diatraea saccharalis (Lepidoptera: Cambridae) caterpillars attack increasing the damage caused by the borer. Two homologous of BARWIN protein were identified in sugarcane, SUGARWIN1 and SUGARWIN2. Their gene expression is induced in response to wound and Diatraea saccharalis damage. However, the recombinant SUGARWIN protein does not affect insect development; but promotes significant morphological and physiological changes in Fusarium verticillioides and Colletotrichum falcatum, which lead to fungal cell death via apoptosis, indicating that SUGARWINs may work as a first layer of defense against the fungi infection. In this study, we deepen our understanding of the role of SUGARWINs in plant defense and the molecular mechanisms by which these proteins affect fungi by elucidating their molecular targets. Our results show that SUGARWINs play an important role in plant defense against opportunistic pathogens. We demonstrated that SUGARWINs are induced by C. falcatum, and the induction of SUGARWINs can vary among sugarcane varieties. The sugarcane variety exhibiting the highest level of SUGARWIN induction exhibited a considerable reduction in C. falcatum infection. Furthermore, SUGARWIN1 exhibited ribonuclease and chitinase activity, whereas SUGARWIN2 exhibited only chitinase activity. This variable enzymatic specificity seems to be the result of divergent amino acid composition within the substrate-binding site. Additionally, plants attacked by insects and pathogens display profound physiological, morphological and chemical changes or adaptations, which may result in organism attraction or avoidance. In this study, we also aimed to understand the insect-fungi association in sugarcane and the role of fungal volatile compounds in this association. Our results have shown that D. saccharalis positively influences C. falcatum infection on sugarcane, inducing a fast growing when compared to C. falcatum treatment without D. saccharalis attack. In addition, both fungi, C. falcatum and F. verticillioides, have been shown a double effect on D. saccharalis caterpillar, they promoted a strong attraction for insects due volatile organic compound emission and positively influenced D. saccharalis feeding and weight gain in diets supplemented with fungi. Fungal volatile organic compounds from C. falcatum and F. verticillioides were identified and quantified; acoradiene and acorenol were specifically induced by the fungi. These data suggest a synergistic interaction, mediated by organic volatile compounds, between D. saccharalis and the fungi C. falcatum and F. verticillioides in sugarcane.